First Spatial Reconstruction of Past Fires in Temperate Europe Suggests Large Variability of Fire Sizes and an Important Role of Human-Related Ignitions - Zin, Ewa; Kuberski, Łukasz; Drobyshev, Igor; Niklasson, Mats (Frontiers in Ecology and Evolution, 2022)
The spatial component of past forest fires in temperate Europe has been little studied, despite the value of such data in quantifying human and natural factors driving fire activity and associated forest dynamics. Changes in fire regimes reported across a range of ecosystems call for a better understanding of variability in historic fires and may help define reference points that can be relied upon when discussing climate change effects. We provide the first dendrochronological reconstruction of historical fire sizes in Central Europe and analyze the minimum extent of fires during the last four centuries in a 9.2 km2 (920 ha) conifer-dominated section of Białowieża Forest, one of the largest continuous lowland forests of the subcontinent. We recorded 82 fires between 1666and 1946, using 275 sample trees, while 92% of fires (76 out of 82) spread beyond the studied area. Fires varied considerably in size, from events recorded at only one site(1–200 ha) to fires recorded in more than half of the studied area, thus exceeding 500 ha in size. The fire cycle was 11 years over the whole study period, with three distinct periods revealed by the regime shift analysis. In the years 1670–1750, the fire cycle averaged 12 years. It shortened to seven years between 1755–1840 and increased to 22 years over the 1845–1955 period. In comparison with present day data, the reconstructed fire density of 3.2 fires per 100 km2 (10 000 ha) and year exceeded lightning ignition density by one to two orders of magnitude, suggesting a significant contribution of human-related ignitions. Our results highlight the important role of fire disturbance in Białowieża Forest and provide critical baseline information to design biological conservation strategies for European forests.